Prevalence of Dysmenorrhea and Determinants of Menstrual Distress in Adolescent Girls with Dysmenorrhoea, In Tirupati Town - Ravi Sankar Deekala; Sri Aryavalli Akkapeddi; Pravallika Sudharani Rosivari (Medsci Publications, 2022)
Background: Dysmenorrhoea is a common problem during menses in adolescent girls which affects their quality of life, academic activities, cannot attend social functions and use over the counter medicines which may lead to dangerous adverse effects and infertility. Objectives: 1. To study the prevalence of dysmenorrhea in adolescent girls studying in government municipal high schools of Tirupati. 2.To determine the significant factors related to menstrual distress in adolescent girls. Methodology: A cross-sectional study conducted among 320 adolescent girls studying in the selected government high schools of Tirupati, India. The study investigated symptoms, related factors and consequences of menstrual distress in adolescent girls with dysmenorrhea. Four instruments were used to collect data: Questionnaires on Demographic Data, Menstrual Distress Questionnaire, A Questionnaire related to Menstrual characters and A Short Form McGill Pin Questionnaire. Results: Prevalence of dysmenorrhoea among adolescent girls was found 67.7%. Regression analysis indicated that the best subset for predicting menstrual distress in adolescent girls included MPQ-SF, menstrual cycle in days, socioeconomic status and education. Conclusions: Majority (67.7%) of the adolescent girls were suffering with dysmenorrhoea. Menstrual distress is significantly correlated with impact on daily activities, absence from class, and analgesic usage.